THE DIFFERENCE BETWEEN MALE AND FEEMALE SDUTENTS IN CERTAIN TEST WHICH WERE MEASURED BY FOOTSCAN SYSTEM - Danijela Kuna; Ivana Čerkez; Ana Kovačević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Footscan system is an advance technology which allows measuring the pressure applied by a foot on a special platform. With a high speed and resolution, the system allows precise analysis of the pressure discrepancies in all the regions of a foot. With an intention of determining the differences and correlations between the male and female students in the tests for barycenter projection and apportionment of balance through the quadrants of the Footscan system, 32 male and 23 female students between 18 and 20 years of age were tested. Variables causes were constituted by tests for estimation of balance, projections of body's barycenter location, and the foot's status measured on Footscan system. According to the results from the correlation matrix, male students had a larger number of important correlations than female students. Analysis of results from multivariate and univariate analysis of variance, important differences were obtained between examinees in the tests for estimation of the balance on one leg and transformation the barycenter left and right, while the general differences between the subsample were not determined. Obtained differences point to the conclusion that there are disparate mechanisms based on which male and female students function in some tests for determination of balance and projection of the barycenter location